2012
DOI: 10.4194/1303-2712-v12_1_07
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study, which measured the concentrations of Zn, Cu, Pb and Cd, in muscle tissue of 5 commercially important crustacean species (Penaeus monodon, Penaeus indicus, Penaeus semisulcatus, Penaeus marguensis and Metapenaeus brevicornis) collected from the UNESCO declared world heritage site Indian Sundarbans. The Indian Sundarbans at the apex of Bay of Bengal is recognized as one of the most diversified and productive ecosystems in the world located at the confluence of Hooghli-Matla estuarine complex. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Levels of Cu in the muscle and exoskeleton of both male and female lobsters during the three year study shown in Table 2 and Figure 2a, far below the normal permissible range, i.e. 120 ppm as recommended for the crustacean tissue [12]. While in case of lobster eggs, it was found to be higher than the recommended value of Cu in sea food, which is 30 ppm [14].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Levels of Cu in the muscle and exoskeleton of both male and female lobsters during the three year study shown in Table 2 and Figure 2a, far below the normal permissible range, i.e. 120 ppm as recommended for the crustacean tissue [12]. While in case of lobster eggs, it was found to be higher than the recommended value of Cu in sea food, which is 30 ppm [14].…”
Section: Resultsmentioning
confidence: 94%
“…Thus increasing ambient pollution levels in water do not directly affects the marine life. Copper is considered highly toxic metal after mercury and silver in marine life because the existence of a number of detoxifying and storage systems for Cu [12]. Levels of Cu in the muscle and exoskeleton of both male and female lobsters during the three year study shown in Table 2 and Figure 2a, far below the normal permissible range, i.e.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations